Draft Annual Plan 2005-2006 (Statements) Government of Tripura - Planning Commission (Planning Commission, 2005)
Sub-Sector wise proposed outlays, Draft Annual Plan-2004-05 Proposed outlays, Major/Minor Head wise Draft Annual Plan 2004-05 -proposed outlays, Physical Targets and Achievements, Externally Aided Projects, Centrally Sponsored Schemes, PMGY.
Planning (P&C) Department Government of Tripura